Symbolic Interactionism of New Students in New Normal Times: Looking Glass Self through Virtual Class - Urip Mulyadi; Mubarok Mubarok; Agus Triyono (Universitas Islam Sultan Agung, 2023)
The purpose of this study is to understand the interaction with verbal and non-verbal symbols and how the mind and self of new students in the new normal period in personal reflection about themselves through virtual classes. This research is qualitative research with a descriptive research type and uses a constructivist paradigm. Data collection techniques in this study were interviews and literature studies. The theory used is symbolic interactionism theory and computer-mediated communication. The results of the study show, in the context of this mind, most of the informants also started interacting with the two phases, only that they started with the language phase first, namely through chat forums or the Whatsapp (WA) conversation application. Furthermore, in the conversation phase, the informants, after feeling comfortable interacting through text conversations in the WA group, held online forums and actively talked in the video conference. In the context of self-informants, they have realized they have become part of the community, so they constantly combine